Non Invasive Determination of Blood Group Typing Blood Glucose and Haemoglobin Analysis - et. al., Rukkumani V, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Practice of current which is widely used for blood group depend upon the antigen-antibody reaction and for blood glucose and hemoglobin analysis involves needle for pricking blood sample which is painful and can cause discomfort to the patient. All samples test also requires a novel test-strip for blood testing. From this work, non-invasive method for identifying the blood group without pricking the skin. The technique of embeds infrared LED emits infrared radiation; the sensor's output is determined by the photodiode's strength of reception. Linked with intensity range, blood group is identified. The hemoglobin level is measured using near- infrared and average level of blood glucose can be identified using (IR) sensor. Raspberry pi is used as control unit.